A numerical solution of the mechanical bidomain model. Issue 10 (26th July 2016) - Gandhi, Samip; Roth, Bradley J.
Abstract: Introduction : The mechanical bidomain model predicts forces on integrin proteins in the membrane. It has been solved analytically for idealized examples, but a numerical algorithm is needed to address realistic problems. Methods : The bidomain equations are approximated using finite differences. An ischemic region is modeled as a circular area having no active tension, surrounded by normal tissue. Results : The membrane force is large in the ischemic border zone, but is small elsewhere. Strain is distributed widely throughout the ischemic region and surrounding tissue. Conclusion : This calculation provides a testable prediction for the mechanism of mechanotransduction and remodeling in cardiac tissue.